Facial Expressions and Context Effects : A Thesis Presented in Partial Fulfillment of the Requirements for the Degree of of Doctor of Philosophy in Psychology at Massey University, Albany, New Zealand - Xu, Hui (Massey University, 2016)
It is common and important for us to recognise facial expressions in our daily life. Research on recognition of facial expressions was often carried out using isolated faces, which leads us to ignore accompanied contextual information (e.g. vocal sound, body language). Chapter 4 used bodily and vocal expressions as contextual stimuli to investigate whether there are context effects on recognition of all six basic facial expressions. The results generally showed that recognition of facial expressions benefits from congruent contextual stimuli, while recognition of facial expressions is impaired by incongruent contextual stimuli. Chapter 5 examined whether the observed context effects vary with the level of intensity of facial expressions. The results showed that context effects are influenced by the level of intensity of facial expressions and revealed the opposite trend of the magnitude of facilitation effects and interference effects as level of intensity of facial expressions was increased. The following chapter 6 investigated another important aspect of context effects, that is, whether attentional resources influence the observed context effects. The results showed that the magnitude of context effects was reduced when the perceptual load of task-relevant tasks was increased, at least for context effects from bodily expressions to the recognition of disgusted facial expressions. All the data collected showed commonalities and differences in the pattern of context effects on recognition of facial expressions. Future studies might concentrate on the differences among these facial expressions to explore whether there exists a consistent pattern of context effects for all six facial expressions or to refine the existing models regarding recognition of facial expressions to better predict context effects for facial expression recognition.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology